Changes in staff motivation and productivity during the growth process of EGAT : a system dynamics model - Klairung Wongsinsukin; Saeed, Khalid; Weber, Karl E.; Huynh, Ngoc Phien; Shrestha, Ram M.; The Government of Norway (Bangkok : Asian Institute of Technology, 1993)
In an organization, change in staff motivation during the growth process could lead to the counterproductive environment. This kind of problem exists especially in the big organization. Therefore, EGAT is being the case for the simulation study. In aiming to improve the performance or even prevent the counterproductive environment, a system dynamics model is built up as the analytical tool for understanding the internal interaction of the organization. In the model the only factor affecting the staffs' effectiveness is job satisfaction. The job satisfaction is assumed to result by the three factors: complexity, comparative salary, and changing promotion opportunity. Apparently if there exist the relationship between staff salary and income of the organization: and the complexity of the organization can be controlled, the staffs' effectiveness can be improved consequently. The study continues further to investigate the source of the complexity of the working condition. The survey employs the Situational Leadership Theory developed by Hersey & Blanchard (1974). The LASI-self questionnaire is distributed among EGAT's managers by purposive sampling. It found that the organization has a pattern of leadership style in which the coaching is the most familiar style and the directing is the least familiar style. This pattern could lead to the limitation of staffs' responsibility and the generation of complexity. The smvey result rather confirms the outcome of the model. It is the management pattern that generates complexity in the organization. The uncontrolled complexity could lead to the low staffs' motivation which means low staffs productivity. However, the study does not aim to say that the managerial is not good, rather it could be the mismatch between the organization pattern and the culture that creates the problem.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Industrial productivity; Employee motivation